Gestión de peligros y riesgos para tareas con exposición al calor del área de incineración de la empresa Veolia Mosquera. (2021)
When working with exposure to heat, the consequences can be diverse, depending on the health conditions of the people, since all are not suitable to perform correctly in these conditions, so it is important to take this factor into account when accepting a job or develop a project. In this document, a context related to the variables that can occur in the event that people are exposed to extreme temperatures and are not suitable for doing so will be initially displayed